A review on resonant inductive coupling pad design for wireless electric vehicle charging application - Rahulkumar J.; Narayanamoorthi R; Pradeep Vishnuram; C. Balaji; Tomas Gono; Tomas Dockal; Radomir Gono; Petr Krejci (Energy Reports, 2023)
Wireless Resonant Inductive Power Transfer (WRIPT) system is a recently emerging technology for Electrical Vehicles (EVs) charging applications in the automobile industry. WRIPT EV charging system is suitable for low-speed EVs, industrial lift EVs trucks, commercial EVs, marine-operated EVs, and other earth-moving EVs applications. The WRIPT system enables user-friendly EV charging, In-motion WRIPT EV charging system increases the travel range anxiety of the EVs for long distances and reduces the EV charging time duration. Also, this in-motion WRIPT charging system supports the EV with limited onboard battery capacity, with reduced size and weight of the battery. However, this WRIPT EV charging system suffers from low power transfer efficiency (PTE), when the intermediate air gap increases between the Tx and Rx coils or when the coupled coils are misaligned. Hence, designing an efficient magnetic coupling geometrical structure coil for a Tx and Rx power pad is one of the prime requirements of the WRIPT system. This article focuses on presents a review of WRIPT power pads for static and in-motion (quasi-dynamic and dynamic) EV charging applications. It describes the layers in inductive power pad construction arrangement, a selection of materials for developing an effective inductive power pad, and the current state of the art of power pad geometries. Also, the review focuses on WRIPT systems with various power capacities and their parameter specifications, along with prototypes available in various industries globally with system standards. Finally, the challenges with the WRIPT system and its future opportunities or research gaps for investigations are discussed in this article. The main objective of the WRIPT power pad is to achieve a much higher magnetic flux density (B) with minimum coil outer dimension, better tolerance misalignment, and well interoperability performance in coupling architecture. This survey helps the readers to understand the technical implementation of WRIPT coils and identify scientific or technical insights into WRIPT power pads.